Automatic control systems - Golnaraghi, Farid; Kuo, Benjamin C. (New Jersey : John Wiley & Son, Inc., 2010)
Automatic Control Systems provides engineers with a fresh new controls book that places special emphasis on mechatronics. It follows a revolutionary approach by actually including a physical lab. In addition, readers will find authoritative coverage of modern design tools and examples. Current mechatronics applications build motivation to learn the material. Extensive use of virtual lab software is also integrated throughout the chapters. Engineers will gain a strong understand of control systems with the help of modern examples and exercises.
Introduction -- Mathematical foundation -- Block diagrams and signal-flow graphs -- Theoretical foundation and background material: modeling of dynamic systems -- Time-domain analysis of control systems -- The control lab -- Root locus analysis -- Frequency-domain analysis -- Design of control systems -- State variable analysis.
Includes bibliographical references.
Keywords: AUTOMATIC CONTROL